Non-Soy Legumes as Alternative Raw Ingredient for Tempe Production in Indonesia with Additional Health Benefits: a Review - Rahmawati, Della; Gunawan-Puteri, Maria DPT; Santosa, Elena (Journal Akademik Universitas Swiss German, 2021)
The availability of legumes in Indonesia is abundant. Many of them show great potential as an alternative ingredient to suppress the deficiency of nutrient intake. However, the utilization needs to be improved. The aim of this review is to evaluate the potential of selected non-soy legumes which are jack bean, mung bean, red kidney bean, and cowpea based on some consideration such as productivity and their potential to be used as raw ingredient for tempe production related to the nutrient content and functional properties. Despite of the high production of non-soy legumes, the utilization is still considerably low. Several researches stated that non-soy legume shows a great nutrient profile and good functionalities after being processed into tempe. Nutrient content of jack bean, mung bean, red kidney bean, and cowpea were improved due to the removal of antinutrients by the processes involved in tempe production. It shows a similarity and comparability to nutrient content of soybean tempe and even shows better functionality